Optimalisasi Potensi Desa Wisata Nagari Pariangan (Desa Terindah di Dunia) Melalui Peningkatan Kesadaran Masyarakat Dalam Penerapan Protokol Kesehatan Dan Berkoperasi - Boby Febri Krisdianto; Arif Rohman Mansur; Feri Fernandes; Natasya Natasya; Annisa Rahma Yuni (Warta Pengabdian Andalas, 2021)
The Covid-19 pandemic has hurt the tourism sector, including the Tourism Village of Nagari Pariangan. This village was designated as one of the most beautiful villages globally in 2012 due to its nature and culture. Non-natural disasters in the form of Covid-19 impact reducing the number of tourists by 40% in 2020. The purpose of this community service is to help the government of Nagari and tourism managers prepare to adapt to the new era of prevalence through increasing public awareness in the application of health protocols and maximizing the cooperative concept for social business. The activity was carried out using lecture, discussion and demonstration methods regarding (1) Mitigation of tourism disasters due to Covid-19 in order to prevent new clusters in tourist villages, (2) Preparation of health protocols for tourist destinations, (3) Declaration of compliance with health protocols by a leader of the Nagari Pariangan, and (4) Management of cooperative-based tourism villages to strengthen the National Social Safety Net. In addition, the implementation team also handed over posters, banners, booklets, and some equipment that supports hygiene practices at tourist destinations.